2019
DOI: 10.17796/1053-4625-43.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Cure Methods for Intermediate Adhesive Layer on Microleakage of Sealants. An in Vitro Study

Abstract: Background: The objective of this study was to determine the effect of an adhesive layer and its photopolymerization on the microleakage of sealants. Study design: 0.5mm-deep standardized fissurectomies were performed on extracted molars (n = 72). Teeth were randomly assigned to 3 different sealant materials (n = 24/group). Teeth were further divided to receive sealants with or without an adhesive layer. Each sealant with adhesive was also divided into two groups: adhesive was light-cured separately or light c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Mesa et al, and Bagherian et al, concluded that the use of adhesive systems beneath fissure sealants could increase the retention of fissure sealants. 2 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesa et al, and Bagherian et al, concluded that the use of adhesive systems beneath fissure sealants could increase the retention of fissure sealants. 2 , 4 …”
Section: Discussionmentioning
confidence: 99%
“… 3 Also, the adhesive systems beneath fissure sealants can increase retention. 4 So, the study selected to evaluate and compare the effect of subpressure and adhesive system on filled PFS by evaluating microleakage and shear bond strength (SBS) ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…5 The use of adhesive systems beneath fissure sealants can increase the retention. 6 Certain studies have indicated the beneficial effects of adhesive systems on the longevity of fissure sealants. The components within the adhesive can enhance the penetration into the pores of the enamel, thereby enhancing the adhesive strength.…”
Section: Introductionmentioning
confidence: 99%
“…Mesa et al, and Bagherian et al, concluded that the use of adhesive systems beneath fissure sealants can increase the retention of fissure sealants 2,6. Bao et al, also conducted research investigations that demonstrated the effectiveness of using an adhesive system to achieve satisfactory outcomes.…”
mentioning
confidence: 99%